Specialization of antecedent negation loop-rule for a fragment of propositional intuitionistic logic sequent calculus - Alonderis , Romas (Lietuvos matematikos rinkinys, 2009)
The paper deals with specialization of the antecedent negation loop-rule for the negative implication free fragment of the propositional intuitionistic logic.
Keywords: sequent calculus; loop-rule specialization